Detection of Trypanosoma vivax using PCR and LAMP during aparasitemic periods - Cadioli, Fabiano Antonio [UNESP]; Fidelis Junior, Otavio Luiz [UNESP]; Sampaio, Paulo Henrique [UNESP]; Santos, Giuliana Nascimento dos [UNESP]; André, Marcos Rogério [UNESP]; Almeida Castilho, Kayo José Garcia de [UNESP]; Machado, Rosangela Zacarias [UNESP] (Elsevier B. V., 2015)
Trypanosoma vivax affects cattle herds in Africa and Americas and has been spreading rapidly in Brazil, through introduction of animals with subclinical infections and without apparent parasitemia, which makes its diagnosis challenging. PCR and LAMP are effective in detecting the presence of T. vivax DNA in situations of low parasitemia. LAMP is simpler and faster technique than PCR, and can be performed in the field, with limited resources. In this study, the capacities of conventional PCR and LAMP for detecting T. vivax in bovine blood samples classified as aparasitemic were evaluated. The capacity of conventional PCR (56.25%) for detecting positive samples was lower than that of LAMP (93.73%). This may influence the choice of screening tests for cattle herds infected with T. vivax.
Keywords: Elisa; Loop-mediated isothermal amplification; Polymerase chain reaction; Trypanosomiasis